Application of the Rail Vehicle’s Monitoring System in the Process of Suspension Condition Assessment - Melnik, Rafal; Sowinski, Bogdan (Communications - Scientific letters of the University of Zilina, 2013)
Rail vehicle’s suspension determines riding dynamics, safety and comfort. Its condition should be checked regularly, and even monitored continuously. In order to acquire information on suspension condition during commercial operation, the rail vehicles’ monitoring system has been developed at Monitoring of Technical State of Construction and Evaluation of its Lifespan Project (MONIT). The aim of the system is qualitative assessment of suspension condition based on acceleration signals recorded on bogie frames and body. The experimental tests of the system were performed on wagons with introduced suspension damages: stiffness reduction of primary suspension in freight car and the loss of damper of secondary suspension in passenger car. The monitoring procedure and test results are presented in the work.